2018
DOI: 10.1021/acsaem.8b00859
|View full text |Cite
|
Sign up to set email alerts
|

Flow Battery Electroanalysis: Hydrodynamic Voltammetry of Aqueous Fe(III/II) Redox Couples at Polycrystalline Pt and Au

Abstract: The redox flow battery (RFB) is a promising technology for large-scale electrochemical energy storage, but research progress has been hampered by conflicting reports of electron-transfer rates even for well-established battery chemistries. To address this challenge, we are working to deploy established electroanalytical techniques for precise characterization of RFB reaction kinetics. We studied Fe3+/2+ redox chemistry using rotating-disk electrode voltammetry with polycrystalline Pt and Au working electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…We are working to understand, and ultimately eliminate, kinetic limitations in RFBs by leveraging insights and methods from electroanalytical chemistry to investigate electron transfer in model battery electrolytes. The present study extends on prior results in which we characterized the kinetics of aqueous Fe 3+/2+ as a prototypical RFB positive electrolyte at Pt and Au surfaces using rotating disk electrode (RDE) voltammetry . We have now executed a series of experiments examining the electron-transfer kinetics of the Fe 3+/2+ redox couple at GC electrodes as a function of surface preparation.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…We are working to understand, and ultimately eliminate, kinetic limitations in RFBs by leveraging insights and methods from electroanalytical chemistry to investigate electron transfer in model battery electrolytes. The present study extends on prior results in which we characterized the kinetics of aqueous Fe 3+/2+ as a prototypical RFB positive electrolyte at Pt and Au surfaces using rotating disk electrode (RDE) voltammetry . We have now executed a series of experiments examining the electron-transfer kinetics of the Fe 3+/2+ redox couple at GC electrodes as a function of surface preparation.…”
Section: Introductionmentioning
confidence: 54%
“…In the context of RFB device engineering, it is apparent that transition metal aquo complexes do not behave as outer-sphere electron-transfer reagents but instead exhibit remarkably complex interfacial redox chemistry. Our results suggest that only certain types of oxidized carbon surface sites competently catalyze electron transfer to/from Fe 3+/2+ (aq), and the catalytic requirements of carbon substantially diverge from those of noble metals. , Analogous work on vanadium redox chemistry has also shown widely variable results depending on the specific method that is used to modify the surface chemistry of carbon electrodes. For example, Bourke et al found that vanadium RFB electron transfer can be either enhanced or suppressed by electrochemical surface modifications depending on whether the treatment is oxidizing or reducing and whether the electrolyte of interest is V 3+/2+ or V 5+/4+ . , Zeng et al reported that oxygen-containing functional groups that were generated using an alkaline hydrothermal treatment catalyze the V 3+/2+ redox reaction but have no significant influence on the kinetics of V 5+/4+ .…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations